Inhibitory effects of chitosan-based coatings on endogenous enzyme activities, proteolytic degradation and texture softening of grass carp (Ctenopharyngodon idellus) fillets stored at 4 °C. (1st October 2018) - Yu, Dawei; Regenstein, Joe M.; Zang, Jinhong; Xia, Wenshui; Xu, Yanshun; Jiang, Qixing; Yang, Fang
Highlights: Effects of chitosan-based coatings to proteolysis and endogenous enzyme activities of grass carp fillets were studied. Chitosan-based coatings significantly inhibited the activities of cathepsin B, B + L and calpain. Coating treatments were effective in impeding protein degradation and softening of refrigerated fillets. Abstract: The study evaluated the inhibitory effects of chitosan-based coatings on endogenous enzyme activities, proteolytic degradation and texture softening of grass carp ( Ctenopharyngodon idellus ) fillets stored at 4 °C for 15 days. In general, the inhibitory effects of chitosan coating were worse than that of chitosan composite coatings, which significantly inhibited cathepsin B, B + L and calpain activities of fillets, with the most reductions of 58%, 65% and 41%, respectively when compared to the corresponding values of control fillets. Besides, the treatments also retarded the proteolytic degradation through quantifiable indicators including salt-soluble proteins (SSP), TCA-soluble peptides and SDS-PAGE pattern. After storage of 15 days, the shear forces of coated fillets were 28–53% higher than that of control samples. These results indicated that chitosan composite coating combined with glycerol monolaurate and clove essential oil improved the quality of refrigerated grass carp fillets by alleviating endogenous enzyme induced proteolysis and softening.